Analysis of Investment Strategy Composition in Rental of Electric Forklift and Diesel Forklift (Case Study of PT XYZ) - Setiawan, Billy; Siallagan, Manahan Parlindungan Saragih (Publikasi Indonesia, 2025)
Global initiatives like the Paris Agreement encourage industries worldwide to adopt sustainable practices, including transitioning from diesel-powered to electric-powered machinery. PT XYZ, a company in the logistics sector, faces strategic investment decisions regarding the optimal composition between electric and diesel forklifts. This study aims to determine the most effective investment strategy using the Analytic Hierarchy Process (AHP), supported by a mixed-methods approach combining stakeholder interviews and quantitative pairwise comparisons. The analysis evaluates five primary criteria—Environmental Impact, Economic Efficiency, Operational Performance, Regulatory Compliance, and Market Preference—and fifteen sub-criteria. Findings indicate that Economic Efficiency is the most dominant criterion (52.3%), with Operating Cost (34%) as the leading sub-criterion favoring electric forklifts. The optimal investment ratio is 65.78% electric forklifts and 34.22% diesel forklifts, enabling the acquisition of approximately 67 electric and 51 diesel units with an investment of IDR 30 billion. This composition supports a rental strategy with a potential return on investment in under two years. Diesel forklifts remain advantageous in operational capacity and infrastructure compatibility, especially in remote areas. The AHP model was validated with CR values <0.1, indicating consistent decision-making inputs. The study contributes to strategic investment modeling in the Indonesian industrial sector, aligning business practices with sustainability goals. It also suggests future research exploring dynamic decision-making models, lifecycle cost analysis, and infrastructure readiness assessments for wider adoption of electric forklifts.